2017
DOI: 10.1016/j.jaad.2017.01.044
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oral Polypodium leucotomos extract on ultraviolet B response: A human clinical study

Abstract: Background Systemic antioxidants, such as oral Polypodium leucotomos extract (PLE), have been found to have photoprotective properties. Objective This study was designed to objectively evaluate the molecular and photobiologic effects of oral administration of PLE. Methods 22 subjects with Fitzpatrick skin phototype I–III were enrolled. On day 1, subjects were irradiated with visible light, ultraviolet A1 (UVA1) and ultraviolet B (UVB; using 308-nm excimer laser). Evaluation was done immediately and 24 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 23 publications
0
52
0
5
Order By: Relevance
“…Colorimetry and DRS are noninvasive objective assessment techniques used to quantitatively assess erythema and pigmentation . The details of the equipment have been described previously and are also included in Materials and Methods S1 (see Supporting Information) . In this study, colorimetric analysis focused on the magnitude of the change in L* (−ΔL*).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorimetry and DRS are noninvasive objective assessment techniques used to quantitatively assess erythema and pigmentation . The details of the equipment have been described previously and are also included in Materials and Methods S1 (see Supporting Information) . In this study, colorimetric analysis focused on the magnitude of the change in L* (−ΔL*).…”
Section: Methodsmentioning
confidence: 99%
“…9,10 The details of the equipment have been described previously and are also included in Materials and Methods S1 (see Supporting Information). 11,12 In this study, colorimetric analysis focused on the magnitude of the change in L* (ÀDL*). The greater the magnitude of ÀDL*, the darker the lesion.…”
Section: Assessmentsmentioning
confidence: 99%
“…Participants had significantly higher MED post-treatment (i.e., their skin required a higher UV dose to induce redness) compared to pre-treatment. In a recent study, Kohli et al reported on the clinical and histological effects of oral PLE on irradiation with a combination of UVA/UVB and visible light 142 . On day 1, 22 patients (Fitzpatrick skin type I–III) were irradiated and MED determinations were made on day 2.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, oral intake of nicotinamide prevents photo-immunosuppression and development of actinic keratoses and keratinocyte cancers in humans, 50,51 and oral intake of carotenoids, or Polypodium leucocotmos can reduce UVB-induced erythema. 52,53 We believe that the photoprotective potential of oral photoprotection has not yet been fully realized and should be further investigated. For regulatory reasons, in the past the emphasis has been on the prevention of UVB-induced erythema, similar to sunscreens.…”
Section: Potential For Oral and Systemic Photoprotectionmentioning
confidence: 99%
“…Nutritional supplements may contain one or more actives that promote skin photoprotection through different mechanisms and could thereby complement topical sunscreens. As an example, oral intake of nicotinamide prevents photo‐immunosuppression and development of actinic keratoses and keratinocyte cancers in humans, and oral intake of carotenoids, or Polypodium leucocotmos can reduce UVB‐induced erythema . We believe that the photoprotective potential of oral photoprotection has not yet been fully realized and should be further investigated.…”
Section: Introductionmentioning
confidence: 98%